Thyroid Dysfunction Risk After Iodinated Contrast Media Administration: A Prospective Longitudinal Cohort Analysis - Sohn, Seo Young; Inoue, Kosuke; Bashir, Muhammad T; Currier, Jesse W; Neverova, Natalia V; Ebrahimi, Ramin; Rhee, Connie M; Lee, Martin L; Leung, Angela M (The journal of clinical endocrinology and metabolism, 2025)
Iodinated contrast media (ICM) is a common source of excess iodine in medical settings, given the common use of iodinated radiologic procedures. To determine the long-term risks of thyroid dysfunction following iodinated contrast administration in a prospective study. A longitudinal cohort study was conducted of patients in the United States Veterans Affairs medical system who received ICM. Serum thyroid function, thyroid antibody, and inflammatory markers were measured at baseline. Thyroid function tests were repeated at 1 month, 3 months, and every 6 months thereafter until 36 months. Risk of thyroid dysfunction and longitudinal changes in thyroid hormone levels were assessed using mixed effect models. There were 122 participants (median age, 70.0 [interquartile range 62.2-74.0] years; 98.4% male). At baseline, 6 subjects had subclinical thyroid dysfunction prior to ICM receipt. During median follow-up of 18 months, iodine-induced thyroid dysfunction was observed in 11.5% (14/122); 6 (4.9%) developed hyperthyroidism (including 1 with overt hyperthyroidism) and 8 (6.6%) subclinical hypothyroidism. At last follow-up, 10 of 20 subjects with thyroid dysfunction (14 new-onset cases and 6 with preexisting thyroid dysfunction) had persistent subclinical hyperthyroidism or hypothyroidism. There were also subtle changes in thyroid hormones observed longitudinally within the reference ranges in the overall cohort. There is a rare long-term risk of an excess iodine load on thyroid dysfunction even among individuals from an overall iodine-sufficient region, supporting the need for targeted monitoring following iodinated contrast administration.